Transitivity Analysis of The Main Character in Front Desk: Linguistic Portraits of Racial Dynamics in Young Adult Fiction - Nirwana; Mustafa, Mutakhirani; Muhlis (Universitas Tidar, 2024)
This article applies Systemic Functional Linguistics (SFL) to conduct a transitivity study of racial prejudice depiction in Kelly Yang's young adult fiction novel